2022
DOI: 10.1016/j.jtocrr.2021.100265
|View full text |Cite
|
Sign up to set email alerts
|

A Real-World Study on the Effectiveness and Safety of Pembrolizumab Plus Chemotherapy for Nonsquamous NSCLC

Abstract: Introduction The real-world effectiveness of combination treatment with cytotoxic chemotherapy and programmed cell death protein-1 or programmed death-ligand 1 inhibitor for NSCLC, especially for the elderly (aged ≥75 y) or those with poor performance status (≥2), has not been fully elucidated. We investigated the real-world effectiveness and safety of this combination therapy in these populations. Methods This multicenter retrospective study evaluated patients who are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 29 publications
2
22
1
Order By: Relevance
“…In patients with nonsquamous NSCLC, poor ECOG-PS has been found to be a poor prognostic factor in patients receiving pembrolizumab plus chemotherapy. 10 In a retrospective data analysis, chemotherapy plus atezolizumab for patients with ES-SCLC with a PS of more than or equal to 2 was reported to be feasible; however, the OS was short, which is consistent with our present observations. 23 …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In patients with nonsquamous NSCLC, poor ECOG-PS has been found to be a poor prognostic factor in patients receiving pembrolizumab plus chemotherapy. 10 In a retrospective data analysis, chemotherapy plus atezolizumab for patients with ES-SCLC with a PS of more than or equal to 2 was reported to be feasible; however, the OS was short, which is consistent with our present observations. 23 …”
Section: Discussionsupporting
confidence: 91%
“… 5 , 6 , 7 , 8 Nevertheless, elderly (≥75 y old) patients with NSCLC tended to have higher rates of treatment discontinuation owing to adverse events (AEs) and severe AEs, including pneumonitis. 9 , 10 …”
Section: Introductionmentioning
confidence: 99%
“…Most patient had adenocarcinoma, were tobacco smokers, and had an ECOG PS 0 to 1. No difference in OS and PFS was found between patients > 75 and < 75, but after stratifying patients by age groups (<65, 65 to 74, ≥ 75) a trend of increased rates of severe AEs (16%, 21%, and 26%, respectively) and treatment discontinuation due to AEs (14%, 27%, and 40%, respectively) was observed [63].…”
Section: Immune Checkpoint Blockers In Combination Regimensmentioning
confidence: 84%
“…A recently published multicenter retrospective cohort study reported of 299 patients with treatment-naïve NSCLC who received platinum, pemetrexed and pembrolizumab [63]. The median age was 68; 43 elderly patients (14%) were included.…”
Section: Immune Checkpoint Blockers In Combination Regimensmentioning
confidence: 99%
See 1 more Smart Citation